2001
DOI: 10.1007/bf00766710
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mechanical properties of wood during a period of moisture conditioning

Abstract: Changes in the modulus of elasticity (MOE), modulus of rupture (MOR), and stress relaxation in the radial direction of wood (hinoki: Chamaecyparis obtusa) moisture-conditioned by the adsorption process from a dry state and by the desorption process from a moisture content slightly below the fiber saturation point were investigated. The MOE and MOR of wood conditioned by the adsorption process showed significant increases during the later stages of conditioning when the moisture content scarcely changed. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
1
13
0
1
Order By: Relevance
“…Wood-water interactions and its influence on dynamical mechanical properties are already well documented (Ebrahimzadeh and Bertilsson 1998). The final modifications of E′ and tanδ after impregnation with water are comparable to the results obtained by Ishimaru et al (2001b) and Obataya et al (1998). For ethanol, as no Evolution of viscoelastic properties of poplar veneers specimens immersed in pure water and pure ethanol at 40 °C.…”
Section: Pure Solventssupporting
confidence: 60%
“…Wood-water interactions and its influence on dynamical mechanical properties are already well documented (Ebrahimzadeh and Bertilsson 1998). The final modifications of E′ and tanδ after impregnation with water are comparable to the results obtained by Ishimaru et al (2001b) and Obataya et al (1998). For ethanol, as no Evolution of viscoelastic properties of poplar veneers specimens immersed in pure water and pure ethanol at 40 °C.…”
Section: Pure Solventssupporting
confidence: 60%
“…Recently, it has been demonstrated that MOE also depends on the moisture-conditioning period, even if the wood has the same MC and is at the same temperature (Ishimaru et al 2001b). It was reported that woods stored under various relative humidities (RHs) reach equilibrium MC after approximately 3 weeks, but the MOE continued to increase gradually, even after 9 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto a los ciclos ambientales, durante el segundo ciclo, tanto en invierno como en verano, la dureza en la pared celular de los tres tratamientos, aumentó en promedio un 12%. Ishimaru et al (2001) sugirieron que el incremento de las propiedades mecánicas en la madera tras haber pasado por varios cambios cíclicos de humedad, estaría asociado a una reorientación de las cadenas moleculares de las componentes de la madera, puesto que éstas intentan alcanzar una estabilidad en estos procesos.…”
Section: Dureza Obtenida Por Nanoindentacionesunclassified